Emergencies in systemic lupus erythematosus - Senem Tekeoğlu; Gökhan Keser (Ulusal Romatoloji Dergisi)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with multi-organ involvement, characterized by periods of remission and flares. Severe disease manifestations and complications of immunosuppressive therapy are common reasons for emergency department visits. Nephrological, neurological, pulmonary, and hematological involvement may require urgent intervention. Lupus nephritis, thrombotic microangiopathy, and antiphospholipid syndrome can cause significant renal dysfunction. Neurological complications include stroke, seizures, neuropsychiatric lupus, and central nervous system vasculitis. Pulmonary emergencies such as acute lupus pneumonitis, diffuse alveolar hemorrhage, and pulmonary embolism are life-threatening, while cardiac involvement includes pericarditis, myocarditis, and accelerated atherosclerosis. Hematologic complications, including autoimmune hemolytic anemia, thrombocytopenia, and macrophage activation syndrome, are associated with high mortality. Infections are common in immunosuppressed patients and can mimic disease flares. During pregnancy, complications such as preeclampsia, Hemolysis, Elevated Liver enzymes, Low Platelets syndrome, neonatal lupus, and antiphospholipid syndrome-related thrombosis may arise. The management of SLE emergencies requires a multidisciplinary approach. Individualized treatment strategies following current guidelines and early intervention are crucial in reducing mortality.